Diagnostic value of loop-mediated isothermal amplification in detecting lower respiratory pathogens - Ya Wen; Juan Huang; Yanjia Du; Zishuang Zhong; Hanhua Zeng; Weiqiang Zhang (Journal of Infection in Developing Countries)
Introduction: To investigate the diagnostic value of loop-mediated thermostatic amplification (LAMP) in detecting pathogenic bacteria from bronchoalveolar lavage fluid (BALF) of patients with pulmonary disorders combined with lower respiratory tract infections (LRTI).